Male and Female Lecturer’s Metaphorical Talks in University EFL Classrooms - Sutrismi, Sutrismi; Atmowardoyo, Haryanto; Nur, Sahril (Celebes Journal of Language Studies, 2022)
People’s social background and empirical knowledge firmly determine their metaphors (Lakoff & Johnsen, 2003: Kovecses, 2010). Since in general men and women have different social experiences and views of life, it is highly assumed that metaphors are strongly influenced by gender. This article explores how gender influences lecturers’ metaphorical talks in Indonesian university EFL classrooms and how the figurative talks contribute towards the classroom learning process. It goes over findings of a case study undertaken at a university in Makassar, Indonesia. The findings reveal that the female lecturer’s metaphorical talks are more complex than the male lecturer’s, implying that the female has more critical thinking. In general, the metaphorical talks given by both sides contribute towards the knowledge acquisition process in the classrooms in that they lead the students to understand the lecturers’ certain ideas.